Class for Mothers of Toddlers to increase knowledge about Stunting - Masiyaroh, Maisyaroh; Febrianty, Feny; Hotna, Hotna (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
World Health Organization (2014), stunting is considered an irreversible growth disorder which is mostly influenced by inadequate nutritional intake and recurrent infections during the first 1000 days of life. Based on incidence, stunting is mild if the prevalence is between 20%-29%, it is said to be moderate if it is between 30%-39% and it is said to be severe if it is > ͢ 40%. The method used in this research is a quasi experiment. The design used is a one group pre test and post test design, which is a research design that is used by giving an initial test and a final test to a single group research sample. The research design is one group pre test and post test design. The sample in the research was total sampling, that is, all mothers who had babies aged 0-5 years were sampled, namely 42 mothers. The data collection method uses primary data collected through a questionnaire in the form of closed ended questions which are formed with multiple choices, namely by providing several answers/alternatives, and the respondent only chooses one of them that is in accordance with his opinion. Based on the results of bivariate analysis using the paired t test, the p value = 0.001 (p <0.05) with a confidence level of 95%. This p value statistically shows that there is an influence of Booklet Media on Increasing Mothers' Knowledge in Stunting Prevention in Selat Lancang Subdistrict in 2023. Conclusion: There is an Influence of Booklet Media on Increasing Maternal Knowledge in Stunting Prevention in Selat Lancang Subdistrict in 2023 with a total of 42 respondents. significant relationship with a p value of 0.001.